The Impact of Audio-Visual-Based Learning Media on Freestyle Swimming Ability - Raswin, Raswin; Nasution, Usman (LP. Ma'arif Janggan Magetan, 2025)
This research investigates the impact of audio-visual-based learning media on the freestyle swimming abilities of junior high school students in Medan City. Employing a quantitative approach with a weak experimental method, the study used a One Group Pre-test-Post-test design involving 29 students. Data were analyzed using IBM SPSS Statistics. The knowledge pre-test showed a minimum score of 20.00, a maximum of 80.00, an average of 57.25, and a standard deviation of 13.48. Post-test knowledge scores improved, with a minimum of 80.00, a maximum of 100.00, an average of 74.45, and a standard deviation of 7.59. For skills, pre-test results showed a minimum of 4.00, a maximum of 10.00, a mean of 4.26, and a standard deviation of 2.10. Post-test results showed improvements with a minimum of 6.00, a maximum of 15.00, a mean of 7.45, and a standard deviation of 3.08. The findings indicate that using audio-visual media significantly improved student learning outcomes in freestyle swimming, with knowledge increasing by 51.80% and skills by 31.55%.